The ugly history of beautiful things : essays on desire and consumption - Kelleher, Katy (Simon & Schuster, 2023)
In these deeply researched essays, a Paris Review contributor blends science, history, and memoir to explore human obsession with gorgeous things, exposing the fraught histories of makeup, silk, jewels, perfume, and other objects, helping readers to ethically partake in the beauty of the world around them.